2018
DOI: 10.1080/10888438.2018.1529767
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attribution Profiles as a Function of Reading Skills, Hyperactivity, and Inattention

Abstract: The causes that individuals attribute to reading outcomes shape future behaviors, including engagement or persistence with learning tasks. Although previous reading motivation research has examined differences between typical and struggling readers, there may be unique dynamics related to varying levels of reading and attention skills. Using latent profile analysis, we found 4 groups informed by internal attributions to ability and effort. Reading skills, inattention, and hyperactivity/impulsivity were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
0
13
0
2
Order By: Relevance
“…A low sense of competence and poor motivation are known to characterize youth with persistent learning difficulties, leading to lower engagement with reading development and literacy-related tasks (Chapman et al, 2000; Morgan et al, 2008; Tsujimoto et al, 2019, 2018; Zentall, 2012). Accordingly, since the very first iteration, the PHAST interventions have targeted maladaptive attributions and motivational beliefs (Lovett et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A low sense of competence and poor motivation are known to characterize youth with persistent learning difficulties, leading to lower engagement with reading development and literacy-related tasks (Chapman et al, 2000; Morgan et al, 2008; Tsujimoto et al, 2019, 2018; Zentall, 2012). Accordingly, since the very first iteration, the PHAST interventions have targeted maladaptive attributions and motivational beliefs (Lovett et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strength of this relationship increased with increasing reading skill for three of four reading measures. Tsujimoto and colleagues (Tsujimoto et al, 2019(Tsujimoto et al, , 2018 also showed that a failure to attribute successes to ability was strongly associated with age and with degree of reading impairment.…”
Section: Motivational Aspects Of Reading Impairment In Adolescence: A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Students are taught to read aloud syllables, words, labels, and simple sentences [18], [19]. Students are also trained to read voices (fluently) simple sentences consisting of 3-5 words with attention to pronunciation and correct intonation, pause (to stop, inhale): long or short pauses, giving emphasis to certain words according to the context, and starting identifying keywords from rather long readings [20].…”
Section: Results Of Analysis Of Literature Studies About Early Readinmentioning
confidence: 99%
“…Notably, research consistently points out the need for increasing motivation in adolescent learners, since motivation declines with age (Kamil et al, 2008; Lovett et al, 2021). Further, many students with learning disabilities experience a lower sense of competence, which can lead to lower engagement (Tsujimoto et al, 2019). Luckily, Lämsä et al (2018) found that gamification elements have the potential to engage learners in literacy interventions and can improve basic reading skills.…”
Section: Introductionmentioning
confidence: 99%